Bunk Space Requirements for Growing Beef Cattle Limit-Fed a High-Energy Corn and Corn Co-Product Diet - Z. M. Duncan; Z. L. DeBord; M. G. Pflughoeft; K. J. Suhr; W. R. Hollenbeck; K C Olson; D. A. Blasi (Kansas Agricultural Experiment Station Research Reports, 2022)
Objective:The objective of our experiment was to evaluate the effects of bunk allotment on performance of growing beef calves during a 58-day receiving period and investigate possible residual effects of bunk-space allotment on subsequent growth performance during a 90-day grazing season. Study Description:A group of 385 crossbred steers (initial weight 473 ± 56 lb) were purchased in Texas and transported to the Kansas State University Beef Stocker Unit. Calves were blocked by arrival date, assigned to one of four bunk space treatments (i.e., 10, 15, 20, or 25 in of bunk per head), and limit-fed a high-energy corn and corn co-product diet for 58 days. Following the receiving period, steers were blocked by bunk-space treatment, randomly assigned to one of eighteen pastures, and grazed for 90 days. The Bottom Line:We interpreted our data to suggest that bunk allotments of 10, 15, 20, or 25 in per calf had minimal impact on growth performance during a 58-day receiving period and did not affect final body weights following a 90-day grazing season.
Keywords: limit feeding; bunk requirements; growing cattle